2020
DOI: 10.1021/acs.jpclett.0c01975
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Nature of Colloids in Methylammonium Lead Halide Perovskite Precursor Inks Revealed by Cryo-Electron Microscopy

Abstract: Metal halide perovskites have generated interest across many fields for the impressive optoelectronic properties achievable in films produced using facile solution-processing techniques. Previous research has revealed the colloidal nature of perovskite precursor inks and established a relationship between the colloid distribution and the film optoelectronic quality. Yet, the identity of colloids remains unknown, hindering our understanding of their role in perovskite crystallization. Here, we investigate precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The removal of the bulk solvent molecules is expected to lead to a drastic reduction in the excluded free volume available for the solute molecules and cause a pinned gel-like structure 21,66 with decreased diffusion abilities. The stochastic nature 61,70 of nucleation of the perovskite precursor colloid 37,71 , where a broad distribution of nuclei sizes are expected at supersaturation, is reflected in the evolution of the PL FWHM. Whereas antisolvent-driven nucleation is expected to lead to a homogenous nucleation event, suggest that the actual nature of nucleation depends on the time window employed for antisolvent dispensing 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the bulk solvent molecules is expected to lead to a drastic reduction in the excluded free volume available for the solute molecules and cause a pinned gel-like structure 21,66 with decreased diffusion abilities. The stochastic nature 61,70 of nucleation of the perovskite precursor colloid 37,71 , where a broad distribution of nuclei sizes are expected at supersaturation, is reflected in the evolution of the PL FWHM. Whereas antisolvent-driven nucleation is expected to lead to a homogenous nucleation event, suggest that the actual nature of nucleation depends on the time window employed for antisolvent dispensing 19 .…”
Section: Discussionmentioning
confidence: 99%
“…One example is anion additives such as chloride, which is widely known to modify the crystallization process and has become a commonly used additive to make high efficiency -FAPbI 3 -based solar cells. Recent XRD (39) and cryo-electron microscopy (40) experiments have shown that chloride induces a quasi-2D-like intermediate phase that can help in the nucleation of -FAPbI 3 . Therefore, the current theoretical approach presented here can be applied to unravel the effects of different additives.…”
Section: Discussionmentioning
confidence: 99%
“…13 Methods preferably used for solution characterization, like dynamic light scattering (DLS), UV-vis spectroscopy or cryogenic transmission electron microscopy (cryo-TEM) should be used with caution, as often the nature of the regarded system slightly differs, or crucial properties are only indirectly determined. 5,7,[14][15][16] Considering the origin of biochemical solutions (e.g. micelle formation), DLS is particularly suitable to detect larger nanostructures in the range of 5 to 1000 nm.…”
mentioning
confidence: 99%
“…Whereas Kim et al refer to colloidal sizes in the range of 100 nm based on DLS studies, 5,18 the first study using cryo-TEM reveals first insights on the size of the colloidal structures found in the perovskite precursor solutions, which are in the range of 1 nm. 14 Still, it remains unclear what effect the cryo shock freezing has on the nature of the colloid chemistry in solution. 19 Unfortunately, also the colloidal interactions in liquid are not considered.…”
mentioning
confidence: 99%